PENGARUH PENGUNGKAPAN SOSIAL DAN LINGKUNGAN TERHADAP ASIMETRI INFORMASI BAGI INVESTOR (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2012-2013) - Febi Almira, Lida; Fuad, Fuad (Diponegoro Journal of Accounting, 2015)
This research aimed to examine the effect of disclosure of social and environmental disclosure to the asymmetry of information in the annual report issued by the company. This research examinedthe annual reports of 100 companies that perform voluntary disclosure is  disclosure of social and environmental disclosure in the Indonesia Stock Exchange since 2012-2013. Disclosure of socialand environmental disclosure be investigated by using the method of content analysis. The research uses secondary data based on random sampling method. Method of data processing using a linear OLS regression with a significant level of 10%. The results show that the disclosure of social andenvironmental  disclosure  affect  the  asymmetry  of  information  in  the  annual  report  and  each disclosure  have  a  negative  direction,  which  means  the  higher  the  disclosure  of  social  andenvironmental disclosure will reduce the asymmetry of information.